Penentuan Suhu Optimum Pirolisis Serbuk Gergaji Batang Kelapa: Determination of the Optimum Temperature of the Pyrolysis of Coconut Trunk Sawdust Waste - Andi Aladin; Takdir Syarif; Andi Suryanto; Andi Magefira; Ardan (KOVALEN: Jurnal Riset Kimia, 2023)
Research has been carried out on the utilization of biomass waste of coconut trunk sawdust using the pyrolysis method to produce two products simultaneously, namely charcoal and liquid smoke. In order to obtain charcoal products with optimum calorific value, it is necessary to understand the optimum pyrolysis conditions. One of the optimum conditions, namely pyrolysis temperature, was studied in this research. Pyrolysis was carried out in a simultaneous pyrolysis reactor at a flow rate of argon inert gas into the reactor of 2 liters/minute and a pyrolysis time of 2.5 hours with pyrolysis temperature variations of 350, 400, 450, and 500Â°C, respectively. The study showed that the optimum temperature of 400oC was obtained which gave a yield of 34% charcoal with a calorific value of 7229 kcal/kg. Compared to the calorific value of the raw material for coconut sawdust which is 4400 kcal/kg, there was an increase in the calorific value of the pyrolysis product by 64%. Based on the optimum temperature condition, liquid smoke as a by-product was also obtained with a yield of 45%. Charcoal can be used as a solid fuel or as a bioadsorbent in the treatment of liquid waste or clarification of liquid food products such as virgin coconut oil (VCO). Grade 3 liquid smoke can be used as a biopesticide, while grade 1 liquid smoke can be used as a food preservative. Given the benefits of the two pyrolysis products, both of the products from the current research have a promising market value.